FAKTOR–FAKTOR YANG MEMENGARUHI SIKAP PEMBELAJAR SEJATI MAHASISWA PROGRAM STUDI PENDIDIKAN AKUNTANSI - Yoanita Intan Palupi; Sudiyanto Sudiyanto; Asri Diah Susanti (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2022)
Abstract The objective of this research is to examine factors that affect learners’ attitudes toward lifelong learning. A quantitative approach with a correlation design is used in this research. Stratified proportional random sampling was employed to determine its samples. They consisted of 194 students of Accounting Education from 2017-2021. Data Analysis used confirmatory factor analysis with structural equation modeling technique by means of the Lisrel 8.80 program. The results of the research show that (1) the family factor had a significant effect on the lifelong learner attitude of the students as indicated by t -statistic value of 2.60; (2) the school factor did not have a significant effect on the lifelong learner attitude of the students as specified by the t-statistic value of 0.59; (3) the social factor did not have a significant effect on the lifelong learner attitude as pointed out by the t-statistic value of 0.07; and (4) the individual factor had a significant effect on the lifelong learner attitude of the students an implied by the tstatistic value of 2.60. Next researchers are recommended to conduct further qualitative research to identify school and social factor indicators that are able to improve the lifelong learner attitude of students expecially in Indonesia. Abstrak Penelitian ini bertujuan untuk mengkaji faktor-faktor yang memengaruhi sikap mahasiswa terhadap pembelajaran sepanjang hayat. Pendekatan kuantitatif dengan desain korelasi digunakan dalam penelitian ini. Teknik sample yang digunakan adalah stratified proportional random sampling, dengan jumlah 194 mahasiswa dari angkatan 2017-2021. Analisis data yang digunakan adalah analisis faktor konfirmatori dengan teknik structural equation modeling menggunakan program Lisrel 8.80. Hasil penelitian menemukan bahwa (1) faktor keluarga berpengaruh signifikan terhadap sikap pembelajar sejati dengan nilai t-statistik 2.60; (2) faktor sekolah tidak berpengaruh signifikan terhadap sikap pembelajar sejati dengan nilai t-statistik 0.59; (3) faktor sosial tidak berpengaruh signifikan terhadap sikap pembelajar sejati dengan nilai t-statistik 0.07; dan (4) faktor individu berpengaruh signifikan terhadap sikap pembelajar sejati dengan nilai t-statistik 2.60. Peneliti selanjutnya direkomendasikan melakukan studi kualitatif lebih lanjut untuk mengidentifikasi indikator faktor sekolah dan sosial yang dapat meningkatkan sikap pembelajar sejati mahasiswa khususnya di Indonesia. . Keywords : lifelong learner attitude, family factor, school factor, social factor, individual factor, SEM-LISREL Kata Kunci : sikap lifelong learner, faktor keluarga, faktor sekolah, faktor sosial, faktor individu, SEM-LISREL